ULTRASOUND USE FOR LISTERIA MONOCYTOGENES ATTACHED CELLS REMOVAL FROM INDUSTRIAL BRINE INJECTION NEEDLES - HAMANN, D.; TONKIEL, K. F.; MATTHIENSEN, A.; ZENI, J.; VALDUGA, E.; PAROUL, N.; STEFFENS, C.; TONIAZZO, G.; CANSIAN, R. (Italian Journal of Food Science, 2018)
This work aimed at studying methods for Listeria monocytogenes attached cells removal from food industry equipment. In order to verify possible contamination points, a tracking was carried out in food products and equipment surfaces (brine injection needles) by swab. Brine injection needles were defined as a study due to their higher contamination potential. L. monocytogenes adhesion after 6 h contact with needles was observed. Minimum bactericidal concentration (MBC) of peracetic acid on L. monocytogenes attached cells was 0.06 and 0.24% with 6 and 24 h contact with bacteria, respectively. 75% power (700 W) and 14 min exposure ultrasound treatment showed a 3.25 Log CFU microbial load reduction in injection needles. The combination of ultrasound and peracetic acid showed an MBC reduction from 0.24 to 0.03%, hence, it may be recommended for meat industry application.